Factors That Affect Employees’ Performance at Concentrix Bridgetowne West, Quezon City: Basis for a Proposed Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employees are now a highly important part of every organization. Employees’ performancesare one of the keys to achieving business goals. Employees are everything to your business,but if your employees are not performing, it undermines all the work you’ve put into yourbusiness. Having great employees can help achieve organizational goals, as stated by SinerizM.H. (2019).The study revealed that most of the employees strongly agree with the factors that affectemployees’ performances in Concentrix Bridgetown West, Quezon City. Based on theassessment of Effectiveness in management, the respondents strongly agree with 3.69 formales and 3.70 for females. The male strongly agrees with 4.29, and the female agrees withthe 3.11 weighted mean that tools and technology can affect employees’ performances.Based on the assessment of the Physical Work Environment, the most affected are females,with 4.00 and 3.99 for males, and the two groups strongly agreed. Moreover, in theassessment of the Digital Work Environment, the male strongly agrees with 4.24 and thefemale with 3.06. It revealed that there is a significant difference between the two groups.The researchers recommend a reward for the good performance of employees, like acertificate for the top performing employees of the month, because it will make employeesperform better and will result in effective management. Providing enough advanced tools andtechnology to be used by the employees and fixing the PCs that are not working well andrunning slowly to increase employees’ performances. Direct communication can solve theethical problems of employees. Using cloud backup to restore or recover the data needed forthe future to organize the files of the organization, and lastly, conducting a review of past andpresent performance of the employees to evaluate the work and improve what needs to beimproved.
Keywords: Business